2020
DOI: 10.1021/acs.organomet.0c00587
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Coordination Modes of Pyridyl-Functionalized N-Heterocyclic Dicarbene Ligands

Abstract: Five palladium(II) complexes bearing potentially tetradentate pyridine-functionalized diNHC ligands with flexible linkers have been synthesized and characterized to study how coordination modes can be controlled by design and electronic factors. A combination of analytical techniques, including single-crystal X-ray diffraction and conductivity measurements, reveal that more strongly donating benzimidazole-derived NHCs induce tridentate coordination to form cationic N,C,C-pincer complexes, while more weakly don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Moreover, N-containing heterocyclic ligands have received intense attention due to their strong coordination affinity to the first-row transition metal ions 6 and their diverse coordination modes. 7 Recent advances in the field of SMMs have shown that 3d metal-based SMMs are still worth pursuing. 8 The oxygen evolution reaction (OER) from water splitting exhibits great promise for clean energy production and shows high potential for replacing conventional fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, N-containing heterocyclic ligands have received intense attention due to their strong coordination affinity to the first-row transition metal ions 6 and their diverse coordination modes. 7 Recent advances in the field of SMMs have shown that 3d metal-based SMMs are still worth pursuing. 8 The oxygen evolution reaction (OER) from water splitting exhibits great promise for clean energy production and shows high potential for replacing conventional fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, N-containing heterocyclic ligands have received intense attention due to their strong coordination affinity to the first-row transition metal ions 6 and their diverse coordination modes. 7 Recent advances in the field of SMMs have shown that 3d metal-based SMMs are still worth pursuing. 8…”
Section: Introductionmentioning
confidence: 99%
“…[ 41,42 ] The stability of these complexes can be further enhanced by the thermodynamic chelate effect such as the case of the chelating bis(NHCs). [ 43–47 ]…”
Section: Introductionmentioning
confidence: 99%